Active surveillance of hepatitis C infection in the UK and Ireland. Issue 4 (1st April 2000) - Gibb, D M; Neave, P E; Tookey, P A; Ramsay, M; Harris, H; Balogun, K; Goldberg, D; Mieli-Vergani, G; Kelly, D
Abstract : AIM: To investigate the prevalence, distribution, and clinical details of paediatric hepatitis C virus (HCV) infection in the UK and Ireland. METHODS: Active monthly surveillance questionnaire study coordinated through the British Paediatric Surveillance Unit, to all consultant paediatricians in 1997 and 1998. RESULTS: A total of 182 HCV infected children were reported from 54 centres and by paediatricians from eight different specialties. In 40 children HCV was acquired through mother to child transmission (MTC children); 142 were infected by contaminated blood products (n = 134), organ transplantation (n = 2), needles (n = 4), or unknown risk factor (n = 2). Intravenous drug use was the risk factor for 35 mothers of MTC children. Twelve children were coinfected with HIV and four with HBV. Recent serum aspartate aminotransferase or alanine aminotransferase values were at least twofold greater than the upper limit of normal in 24 of 152 children; this occurred in five of 11 HIV coinfected children. Liver histology, available in 53 children, showed normal (7%), mild (74%), moderate (17%), or severe (2%) hepatitis. Twenty eight children had received therapy with interferon alfa. CONCLUSION: Most current paediatric HCV infection in UK and Ireland has been acquired from contaminated blood products, and most children are asymptomatic. There is a need for multicentre trials to inform clinical practice and development of good practice guidelines in this area. Long term follow up of this cohort of HCV infected children is planned to help determine the natural history over the long term of HCV acquired during infancy and childhood.